2021
DOI: 10.1093/ehjci/jeaa356.187
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dysfunction parallels left ventricular functional involvement in women with breast cancer experiencing subclinical cardiotoxicity

Abstract: Funding Acknowledgements Type of funding sources: None. Background Cancer therapy related cardiac toxicity disease (CRCTD) of the left ventricle (LV)can influence the outcome of oncologic patients. Little is known on CRCTD related right ventricular (RV)dysfunction even though RV involvement has been proven to be a remarkable prognosticator in heart failure. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the number of reports on this issue has increased in recent years. Interestingly, early RV dysfunction (reduction of RV GLS) paralleled LV involvement and predicted subsequent LV subclinical dysfunction, as demonstrated in breast cancer patients treated with anthracycline, trastuzumab, and paclitaxel [ 11 ]. Laufer-Perl et al reported that CTR-RVT may be even more frequent than CTR-LVT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of reports on this issue has increased in recent years. Interestingly, early RV dysfunction (reduction of RV GLS) paralleled LV involvement and predicted subsequent LV subclinical dysfunction, as demonstrated in breast cancer patients treated with anthracycline, trastuzumab, and paclitaxel [ 11 ]. Laufer-Perl et al reported that CTR-RVT may be even more frequent than CTR-LVT.…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant alterations were observed in the standard echocardiographic parameters of RV function. The longitudinal strain of the left ventricle also decreased significantly, although to a lesser degree [67]. In a retrospective study, Calleja et al (2015) discovered that the patients (n = 30) with proven TIC had poorer RV function than the control group.…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 96%
“…RV dysfunction is not a starting point for defining cardiotoxic events. After sequential therapy with anthracyclines and trastuzumab, Santoro C. et al (2021) discovered that a significant proportion (66%) of patients experienced decreased longitudinal RV function measured via speckle tracking [67]. No statistically significant alterations were observed in the standard echocardiographic parameters of RV function.…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 99%